1984
DOI: 10.1007/bf02441012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying hormonal and precursor supplementations on levels of nicotine and related alkaloids in cell cultures ofNicotiana tabacum

Abstract: Cell cultures ofNicotiana tabacum were grown on M & S medium containing 0-2.0 ppm of two auxins. Cellular nicotine was estimated for given auxin concentrations and highest levels determined. Feeding suspensions with amino acids either alone, or in combination with nicotinic acid and nicotinamide produced decresed nicotine levels. The presence of anatabine, anabasine, myosmine, anatalline and nicotelline in the cultures was established and it was noted that precursor feeding which decreased nicotine concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It has been suggested that anabasine or anatabine is a biosynthetic precursor of anatalline. 45 Anatalline is produced in cell cultures of Nicotiana tobacum , 45,71 at concentrations higher than those of nicotine, and a geometric isomer has been detected as well. 45 In our extracts of tobacco analyzed by GC-MS or LC-MS/MS we did not find evidence of an isomeric substance, although it is possible that an isomer, if present, was not separated by our chromatographic systems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that anabasine or anatabine is a biosynthetic precursor of anatalline. 45 Anatalline is produced in cell cultures of Nicotiana tobacum , 45,71 at concentrations higher than those of nicotine, and a geometric isomer has been detected as well. 45 In our extracts of tobacco analyzed by GC-MS or LC-MS/MS we did not find evidence of an isomeric substance, although it is possible that an isomer, if present, was not separated by our chromatographic systems.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true of alkaloids where, although feeding o f the amino acid precursor may lead to small stimulations in the range of 2-to 5-fold [1,2,3,4,5,6] it is equally likely to have no effect on [7,8,9] or to be detrimental to [10,11] production. This is particularly true of alkaloids where, although feeding o f the amino acid precursor may lead to small stimulations in the range of 2-to 5-fold [1,2,3,4,5,6] it is equally likely to have no effect on [7,8,9] or to be detrimental to [10,11] production.…”
Section: Introductionmentioning
confidence: 99%
“…~~~ A number of attempts have been made to enhance the production of pyridine alkaloids by manipulating the culture medium. Replacement of nitrate with urea increased the 432 The highest yield of nicotine that has been reported thus far (5.3% of the dry weight) was obtained in a photomixotrophic suspension culture of N. tabacum at the end of an optimized three-stage protocol of manipulating the medium. 433 When transferred to a 20-litre-scale batch fermentor, however, the process yielded a much more modest 1 YO of nicotine.…”
Section: Pyridine Alkaloidsmentioning
confidence: 91%